A streetcar named Desire - Williams, Tennessee, 1911-1983 (Methuen drama student editions., 2009)
"A Streetcar Named Desire shows a turbulent confrontation between traditional values in the American South - an old-world graciousness and beauty running decoratively to seed - set against the rough-edged, aggressive materialism of the new world. Through the vividly characterised figures of Southern belle Blanche Dubois, seeking refuge from physical ugliness in decayed gentility, and her brutal brother-in-law Stanley Kowalski, Tennessee Williams dramatises his sense of the South's past as still active and often destructive in modern America. This revised edition features a new production history of the play that considers both stage and screen presentations, an updated bibliography and extensive notes on the language of the play. Commentary and notes by Patricia Hern and Michael Hooper"--About the play.